2015
DOI: 10.1057/bm.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

I love to hate you: Loyalty for disliked brands and the role of nostalgia

Abstract: Brand loyalty has been a popular research area for the previous decades, and concepts such as satisfaction, trust, repurchase behavior and positive brand image have been associated with brand loyalty as antecedents of the concept. This study investigates how much satisfaction actively is required for the development of brand loyalty, focusing on the cases in which loyalty is retained in spite of being disliked. This qualitative study employs 14 semi-structured interviews and for the first time in the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 91 publications
(129 reference statements)
0
16
0
1
Order By: Relevance
“…Limited studies on dislike have answered why consumers dislike a specific brand or its products (Aggarwal & Mcgill, 2012), and what makes a consumer stay loyal to a brand despite disliking it (Demirbag- Kaplan et al, 2015).…”
Section: Dislikementioning
confidence: 99%
“…Limited studies on dislike have answered why consumers dislike a specific brand or its products (Aggarwal & Mcgill, 2012), and what makes a consumer stay loyal to a brand despite disliking it (Demirbag- Kaplan et al, 2015).…”
Section: Dislikementioning
confidence: 99%
“…These studies have provided an understanding of the antecedents and outcomes of brand hate (Bryson, Atwal, & Hultén, 2013;Hegner , Fetscherin, & van Delzen, 2017) alongside its multidimensionality (Zarantonello et al, 2016), how brand hate evolves over time (Zarantonello et al, 2018), how it is related to certain personality traits (Kucuk, 2019), and that there are different types of brand hate (Fetscherin, 2019). However, the literature also outlines milder emotional responses such as brand dislike (Alba & Lutz, 2013;Demirbag-Kaplan, Yildirim, Gulden, & Aktan, 2015;Romani, Grappi, & Dalli, 2012), brand avoidance, brand switching (Gelbrich, 2010;Hogg, Banister, & Stephenson, 2009;Kavaliauskė & Simanaviči utė, 2015;Lee et al, 2009b), or complaining (Halstead & Page, 1992).…”
Section: Need For a Unified Modelmentioning
confidence: 99%
“…Our study identified, described and defined the phenomenon of non-collaborative co-creation to clarify the process by which brand meanings can be subverted during co-creation. In particular, we conceptualised two forms of co-creation: brand play as the playful parodying of brand meanings, as suggested by Fournier and Avery (2011), and brand attack as the expression of negative emotions or even hate for the brand, as identified by Demirbag-Kaplan et al (2015) and Hegner et al (2017). Our study joins a small number of others to explicitly analyse the effect of negative co-creation, for example, those by Echeverri, and Skalen (2011), Gebauer et al (2013) or Greer (2015).…”
Section: Theoretical Implicationsmentioning
confidence: 99%